Horizontal Stand Structure of Community Forests in Cidokom Village Rumpin District Bogor Regency - Yandi, Wahyu Nazri; Rahmilija, Femei; Darsono, Beti Septiana (Cannarium, 2024)
AbstractCommunity forests represent a form of community-based forest resource management that significantly contributes to local economic income, ecological conservation, and climate change mitigation. Cidokom Village, Rumpin Sub-district, Bogor Regency, holds great potential for community forest development. However, data on the horizontal stand structure of community forests in this area remains limited. This study aims to analyze the horizontal stand structure, distribution, and abundance of tree species in the community forests of Cidokom Village to support sustainable management planning. The results show that planting patterns in Cidokom Village's community forests vary, combining timber-yielding trees, fruit trees, and seasonal crops. Timber-yielding species preferred by landowners include sengon and jabon. High tree density in smaller diameters is attributed to inadequate planting spacing and natural regeneration. The horizontal stand structure follows a negative exponential model with an inverted-J pattern, indicating normality for uneven-aged forests, typical of community forests in the study area. This research is expected to enhance the ecological and economic contributions of community forests while serving as a reference for management in other areas with similar characteristics.Keywords: Planting spacing, species composition, tree distribution.